PERHITUNGAN TINGKAT UTANG MAKSIMAL PEMERINTAH SEBAGAI ACUAN BAGI KEBIJAKAN MONETER DI INDONESIA - Doni Satria (Universitas Negeri Padang, 2013)
The interaction of monetary and fiscal policy in an economy played an important role for macroeconomic stabilization policy. Blanchard (1990) has shown the fiscal domination condition in this policy interaction, fiscal dominance condition could be caused by the accumulation of government debt. This research analyzed the maximum debt that can be accumulated by the government, and still be sustained and could not drag the economy to the fiscal dominance condition. Using the Mendoza and Oviedo (2004) model, we find the maximum accumulated government debt is 45.2 percent of Indonesia GDP. This result is based on the 20 percent of expenditure adjustment of Indonesian government budget